Karl Marx - Hunter, Nigel; Higham, Christopher (Est Sussex, England Wayland (Publishers), 1987)
A brief, illustrated, biography of the nineteenth-century German writer and philosopher whose doctrines of socialism and communism influenced workers and leaders throughout the world.
Keywords: Marx, Karl -- 1818-1883.; Marx, Karl -- 1818-1883.; Communism -- History; Communists -- Biography; Philosophers; Communists